Outcomes of Cataract Surgery in Ocular Cicatricial Pemphigoid. (13th August 2013) - Puranik, Charuta J.; Murthy, Somasheila I.; Taneja, Mukesh; Sangwan, Virender S.
Abstract: Purpose : To report the outcomes of cataract surgery in ocular cicatricial pemphigoid (OCP). Setting : L. V. Prasad Eye Institute, Hyderabad, India. Design : Retrospective, interventional case series. Methods : Patients diagnosed with OCP who had undergone cataract surgery were included. Staging of disease, type of surgery, pre- and postoperative best-corrected visual acuity (BCVA), and number and duration of topical and systemic medications were recorded. Complications and any exacerbation or worsening of disease were noted. Results : Nine eyes of 7 patients (3 male, 4 female) were included in the study, with mean age of 60.44 ± 2.6 years (range 56–64 years). Follow-up ranged from 6 months to 10 years (mean 52.9 ± 46.25 months). Surgery performed was extracapsular cataract extraction with posterior chamber intraocular lens implantation ( n  = 5) or phacoemulsification with posterior chamber intraocular lens implantation ( n  = 4). Best-corrected visual acuity improved by more than 2 lines in 6 of 9 (66.67%) eyes, which remained stable till the last follow-up. Three eyes had no visual improvement due to corneal scar in 2 patients and preexisting posterior staphyloma in 1 eye. Disease progression was noted in 2 of 9 operated eyes by one stage at the end of 1 year. Conclusion : In this series, cataract surgery could be safely performed with no major intra- or postoperative complications. While the surgical intervention itself was not associated with acute exacerbations of inflammation, progression of disease was noted in some cases over time. In spite of ongoing disease, cataract surgery in OCP was associated with stable visual outcomes.